Environmental issues of Tourism in Bopath Ella Area - Rewathy, K.; Shameela, M.S.U.; Banu, M.M.N.; Muneera, A.N.F.; Pavithra, V. (Ruhunu University International Conference on Humanities and social sciences, 2017)
Tourism is a powerful economy strength of Sri Lanka. Since the country rich in mineral and natural environment, most of the places attracting the foreigners. Tourism entails the movement of people to countries or places outside their usual environment for personal or business professional purposes. Environmental issues are harmful effects of human activity on the biophysical environment. And also environmental protection is a practice of protecting the natural environment. In this study it dealt with the environmental issues of tourism in Bopathella area. The objectives are to identify the environmental issues in the study area as well as to find the impacts of tourism in Bopathella. Questionnaire survey, Observation and Interviews with the people were used as data collection techniques in order to absorb important information from the selected study area. With a sampling frame of 100 respondents as the representative sample based on simple random sampling method. With the study finally it’s identified such as environmental issues are existing in the study area. Not only due to the tourism but also cause of other human and natural activities. Key Words: Environment Issues, Tourism, Physical Impacts